1987
DOI: 10.1119/1.15065
|View full text |Cite
|
Sign up to set email alerts
|

Neutron irradiation of a NaI(Tl) crystal

Abstract: A series of measurements of nuclear beta and gamma radiation arising in neutron irradiation of a NaI(Tl) crystal is described. These measurements, which employ equipment items available in many advanced undergraduate physics laboratories, permit identification of prominent low-energy prompt gamma radiations produced in the I127(n,γ)I128 reaction as well as certain other radiations interpreted as arising in deexcitation of states in I127 excited by inelastic neutron scattering. In addition, a good determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sharma and Mishra [13] also studied the behavior of energetic radioiodine atoms arising in NaIO 3 -NaNO 3 solid solutions. Rhode [14] performed a series of measurements of nuclear beta and gamma radiation arising in neutron irradiated NaI(Tl) crystal. Islam et al [15] studied the 127 I(n,γ) 128 I reaction and observed 248 transitions in the photon energy range 4.5 -6.8 MeV.…”
mentioning
confidence: 99%
“…Sharma and Mishra [13] also studied the behavior of energetic radioiodine atoms arising in NaIO 3 -NaNO 3 solid solutions. Rhode [14] performed a series of measurements of nuclear beta and gamma radiation arising in neutron irradiated NaI(Tl) crystal. Islam et al [15] studied the 127 I(n,γ) 128 I reaction and observed 248 transitions in the photon energy range 4.5 -6.8 MeV.…”
mentioning
confidence: 99%